I want to solve this differential equation:

$$ C \cdot y(t)\frac{d}{dt} = x(t) - y(t) $$

$x(t)$ and $y(t)$ are two ordinary functions of t, C is a constant - all in in $R$

I am trying to solve it towards $y(t)$. The solution I am looking for looks something like this:

$$ y(t) = e^{\int{x(t)dt}} + C $$

So $\int{x(t)dt}$ can stay - but how will the rest look like and could you show me the individual steps and name the method how to solve it?


If you mean an equation $Cy'(t) = x(t)-y(t)$ then the solution is following.

If $C=0$ then $y = x$. If $C\neq 0$ then $y' + \frac 1 Cy = \frac{x}{C}$. You can solve it by the method "Variation of constant" or "Lagrange method".

  1. Solve the homogeneous equation: $$ y'+\frac{1}{C}y = 0. $$ Separate variables: $$ \frac{dy}{y} = -\frac 1 C dt. $$ By integration we obtain $$ y=K\exp\{-t/C\} $$ where $K$ is some constant.

  2. In Lagrange method you suppose that $K(t)$ is a function rather than a constant and substitute $y=K(t)\exp\{-t/C\}$ in the original equation $y'+\frac 1 C y = \frac x C$ to find $K(t).$ After substituition you obtain: $$ K'\exp\{-t/C\} = \frac{x}{C}, $$ so $$ K' = \frac{1}{C}x(t)\exp\{t/C\} $$ and $$ K = K_1+\frac{1}{C}\int x(t)\exp\{t/C\}dt. $$

Now, $$ y(t) = \left(K_1+\frac{1}{C}\int x(t)\exp\{t/C\}dt\right)\exp\{-t/C\} $$ where $K_1$ is some constant.

By the way, $\exp$ means exponent in this notation, $\exp\{a\} =\mathrm e^a$.

| cite | improve this answer | |
  • $\begingroup$ thank you! In the first equation of (2.): Where did the term "$+\frac{1}{C}y$" go? $\endgroup$ – NW Patrick Jun 24 '11 at 16:00
  • $\begingroup$ More insights found here: voofie.com/content/6/… $\endgroup$ – NW Patrick Jun 25 '11 at 19:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.